SPINA BIFIDA APERTA IN MAHAJANGA: CLINICAL CASES AND LITERATURE REVIEW. - WF Rakotondraibe; RT Andrianaivo; MG Tsiaremby; S Raotoson; NH Raveloharimino; N Rabesandratana; D Andrianarimanana; C Andriamamonjy (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
Introduction The incidence of spinal dysraphism has declined dramatically over the past few decades all over the world; however, the incidence is still much higher in developing countries with low socioeconomic status. Objectives The objective of this study was to describe the epidemioclinical and etiological profile of spina bifida in Mahajanga and report the reality of its management in a precarious environment. Materials and methods The current study includes all patients treated for spina bifida aperta over a three-year period (May 2017- April 2020). Details including demographics, antenatal care history, site and type of lesion, neurological examination, imaging results, associated birth defects, management offered and results were recorded . Results A total of 15 children were operated on for spinal dysraphism during this study period (10 boys and 5 girls). The median age was 2.65 years with an extreme of 2 days and 13 years. Six of the mothers of our patients took Fenugreek (Angamay) as a decoction before conception and during pregnancy and only 5 mothers received folic acid supplementation during pregnancy. We discovered 9 myelomeningoceles, 5 meningocele and one spinalipoma in which the lumbosacral location predominated (40%). Five patients had a ruptured sac at the time of consultation, four children had a local infection, and two had hydrocephalus requiring ventricular bypass. One patient died from ventriculitis. Conclusion SBA remains a major public health problem in developing countries. Its management is complex and requires close multidisciplinary coordination.